An Azerbaijani Adaptation of Tuckman Procrastination Scale: Its Association with Academic Motivation and Self-Efficacy - Bakhtiyar Aliyev; Fuad Asadov; Rahila Mammadova; Nigar Asgerova; Leyla Isayeva; Ulkar Zalova Nuriyeva; Elnur Rustamov (International Journal of Contemporary Educational Research)
The aim of this study was to adapt the Tuckman Procrastination Scale for use with Azerbaijani adolescents and explore the relationships between procrastination, academic motivation and self-efficacy.  Data were obtained from 718 adolescents in Azerbaijan whose ages ranged from 10 to 18 years (M = 13.61, SD = 1.86) through convenience sampling. As part of the adaptation process, confirmatory factor analysis, criterion-related validity, and reliability analyses were conducted. Furthermore, the study shedding light on the relationships between procrastination and academic motivation and self-efficacy were explored using PROCESS macro mediation analysis. The results obtained from confirmatory factor analysis indicated that factor loading values of three items of the scale is less than 30 and cannot be taken into account. The remaining 13 items of Tuckman Procrastination Scale analyzed and confirmed the unidimensional structure of scale.  Internal consistency reliability analysis conducted and the result indicated satisfactory reliability coefficients. Moreover, results demonstrated that procrastination was negatively associated with academic motivation and self-efficacy. Addiction to it, the mediating effect of self-efficacy on the relationship between procrastination and academic self-efficacy was unveiled. These findings suggest that the Azerbaijani version of the Tuckman Procrastination Scale has acceptable  psychometric properties.